As intertextualidades do espaço literário em Francisco Dantas e William Faulkner - Fonsêca, Joseana Souza da (2022)
This thesis compares and explores the construction of literary space in Francisco J. C. Dantas’s and William Faulkner’s novels. For this purpose, theoretical-critical and hermeneutical discussions of literary works are intertwined, in a total of four novels by each author, namely: Cartilha do Silêncio (1997) and Uma Jornada como tantas (2019), texts by the Brazilian novelist and Enquanto Agonizo (1930) - As I Lay Dying and A Mansão (1959) - The Mansion works by the American author. The focus of this research is the social and aesthetic configuration of the literary space from reflections about the identity profiles of the characters and the route through regional, family and psychological territories that cross the literary imagination of each author. In this study, we bring theoretical-methodological approaches that permeate concepts about intertextualities and narrative space. For this purpose, we use Carvalhal and Coutinho’s (2011), Lukács’ (2000), Brandão’s (2013), Foucault (2013), Dardel (2015) and Borges Filho (2017) theories. As a central proposition of this thesis, our aim is to validate the aesthetic and social intertextualities through the eminent structure of the narratives by Dantas and Faulkner, as well as the relation of the human condition with the spatial condition/the place which the individual is part. As main points of this comparative study, we choose the social tensions between the characters and the aesthetic spaces to interpret the social and economic conjuncture that constrain them to decadent and excluding values of regions marked by social prejudice and by the discrimination of the marginalized due to economic segregation. For our studies, Dantas’s andFaulkner's characters are metaphors of an agonizing space, where men and women are lost in daydreams and laments of a bland past and a decadent present. In the agonic space, the spatialized bodies and the embodied spaces reflect, incorporate and reproduce the historical and social structure of the literary chronotope.